1985
DOI: 10.1029/wr021i007p00979
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Water Movement in Unsaturated Porous Materials: 3. Experimental Studies

Abstract: In the first paper of this series a detailed theory was presented in which the principles of hydrodynamic stability analysis were used to develop a linear perturbation equation for vertical water movement with nonsharp fronts. The second paper of the series discussed the application of this analysis to the stability of several soil water systems, some of which were potentially unstable. These included redistribution following infiltration, infiltration into a scale heterogeneous medium, and infiltration into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
75
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 10 publications
7
75
3
Order By: Relevance
“…Even under the condition of a continuous supply of water from the surface, finger flow can be observed by limiting the water flux with alternating layers of overlaying finer material having a lower saturated hydraulic conductivity than the medium and the ponding water [Tabuchi, 1961;Hill and Parlange, 1972;Glass et al, 1989;Baker and Hillel, 1988;Cho and de Rooij, 1999] or by applying a water flux that is lower than the saturated hydraulic conductivity into a uniform medium [Selker et al, 1992a;Yao and Hendrickx, 1996;Kawamoto and Miyazaki, 1999]. However, the occurrence of finger flow is limited to dry granular materials of relatively large [Diment and Watson, 1985] and relatively uniform particle sizes . Moreover, Diment and Watson [1985] showed that the occurrence of finger flow was suppressed by a slight initial water content of about 0.02 by volume, and such a significant effect of the initial moisture on the disappearance of fingers has been confirmed by other experiments [Glass and Nicholl, 1996;Kawamoto and Miyazaki, 1999;Cho and de Rooij, 1999].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even under the condition of a continuous supply of water from the surface, finger flow can be observed by limiting the water flux with alternating layers of overlaying finer material having a lower saturated hydraulic conductivity than the medium and the ponding water [Tabuchi, 1961;Hill and Parlange, 1972;Glass et al, 1989;Baker and Hillel, 1988;Cho and de Rooij, 1999] or by applying a water flux that is lower than the saturated hydraulic conductivity into a uniform medium [Selker et al, 1992a;Yao and Hendrickx, 1996;Kawamoto and Miyazaki, 1999]. However, the occurrence of finger flow is limited to dry granular materials of relatively large [Diment and Watson, 1985] and relatively uniform particle sizes . Moreover, Diment and Watson [1985] showed that the occurrence of finger flow was suppressed by a slight initial water content of about 0.02 by volume, and such a significant effect of the initial moisture on the disappearance of fingers has been confirmed by other experiments [Glass and Nicholl, 1996;Kawamoto and Miyazaki, 1999;Cho and de Rooij, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…However, the occurrence of finger flow is limited to dry granular materials of relatively large [Diment and Watson, 1985] and relatively uniform particle sizes . Moreover, Diment and Watson [1985] showed that the occurrence of finger flow was suppressed by a slight initial water content of about 0.02 by volume, and such a significant effect of the initial moisture on the disappearance of fingers has been confirmed by other experiments [Glass and Nicholl, 1996;Kawamoto and Miyazaki, 1999;Cho and de Rooij, 1999]. Since Hill and Parlange [1972] reported on their detailed observations of this curious phenomenon, much work has been carried out on the conditions of occurrence of finger flow and the structure of fingers.…”
Section: Introductionmentioning
confidence: 99%
“…This affects the quality of groundwater and thus such infiltration studies have aimed to limit the adverse effects of groundwater contamination [2][3][4]. Both laboratory [5,6] and real field experiments [7,8] have confirmed the existence of preferential drainage paths in sandy soils under uniform flow via rainfall or irrigation water. In agricultural applications, when water drains through preferential channels, drainage greatly reduces the quantity of water around the root zone that could otherwise be absorbed by the plants.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experiments have shown that apart from soil structural heterogeneities like macropores [9], preferential paths may also occur in homogeneous dry sand. This is due to the fingering instabilities developing from the interface of a wetting front that occur during initially uniform and gravity-driven fluid flow [5,6,10,11]. This has been observed in homogeneous sandy soil [12][13][14][15] but is nevertheless also proven in materials of varying wettability [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Rather than a compact infiltration front, the flow is often unstable and the water invasion takes the form of preferential flow paths (fingers). Intense experimental and theoretical work on the wetting front instability was initiated in the 70's [48,64,62], and has been followed by numerous measurements of finger formation and unstable gravity-driven infiltration (see, for example, [34,43,69,4,36,72,82,81]). …”
Section: Introductionmentioning
confidence: 99%